Visions of a new land : Soviet film from the Revolution to the Second World War - Widdis, Emma, 1970- (Yale University Press, 2003)
In 1917 the Bolsheviks proclaimed a world remade. This book shows how Soviet cinema encouraged popular support of state initiatives in the years up to the Second World War, helping to create a new Russian identity & territory, an 'imaginary geography' of Sovietness.